Laser cladding copper-based self-lubricating coating applied to wind power sliding bearing and preparation method of laser cladding copper-based self-lubricating coating

By using a mixture of nickel-clad graphite and tin bronze powder in wind-electric sliding bearings and combined with laser cladding technology, the toxicity problem of lead-containing materials in traditional copper-based sliding bearing alloys and the heat loss and metallurgical bonding problems in laser cladding technology are solved, and the copper-based/graphite self-lubricating coating is achieved and the hardness and friction reduction of the coating are improved.

CN119640257APending Publication Date: 2025-03-18SHANGHAI JIAOTONG UNIV +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411818979.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In wind-powered sliding bearings, the lead-containing materials in traditional copper-based sliding bearing alloys are limited due to toxicity and contamination, and the laser cladding process has problems such as heat loss, poor metallurgical bonding, and the coating is prone to cracks and holes when preparing copper-based/graphite self-lubricating coatings.

Method used

The nickel-clad graphite and tin bronze powder are mixed in a specific proportion. After ball milling and drying, a copper-based/graphite self-lubricating coating is prepared using a laser cladding process to improve the bonding strength and forming quality of the coating.

Benefits of technology

The copper-based/graphite self-lubricating coating is achieved with good forming, crack-free, low porosity and good bonding with the substrate, while improving the hardness and friction-reducing properties of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640257A_ABST
    Figure CN119640257A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of metal coatings, and particularly relates to a laser cladding copper-based self-lubricating coating applied to a wind power sliding bearing and a preparation method of the laser cladding copper-based self-lubricating coating, and coating powder comprises the following chemical components in percentage by mass: 1-10% of nickel-coated graphite and the balance of tin bronze. The invention further discloses a preparation method of the coating, and the copper-based composite coating with excellent antifriction and wear resistance is prepared by optimizing the adding amount of nickel-coated graphite and adopting a laser cladding method. Compared with an original tin bronze coating, the hardness of the copper-based self-lubricating coating prepared through the method is improved, and the antifriction performance is obviously improved on the basis that the abrasion resistance is guaranteed. In addition, the coating is good in forming, free of cracks, low in porosity and good in combination with the substrate, and the technical problem that an existing laser cladding process is applied to the copper-based / graphite self-lubricating coating is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal coatings, and in particular to a composition design and a preparation method of a copper-based self-lubricating coating applied to a wind power sliding bearing. Background Art

[0002] Compared with rolling bearings, sliding bearings have obvious technical, market and cost advantages under low speed and high load conditions, so they are increasingly used in wind power bearings. The journal and bushing are two important components of the sliding bearing. During the working process, there is a layer of dynamic oil film between the journal and the bushing to play a role in bearing and lubrication. However, the deformation of the bushing is very likely to be greater than the minimum film thickness, which means that contact friction is easily generated between the journal and the bushing, resulting in bushing burning, shaft seizure and other failures. Therefore, a layer of copper-based sliding bearing alloy with good friction reduction and wear resistance is melted on the surface of the bushing to make the journal-bearing bushing have good friction reduction, compliance and embeddability, thereby reducing wear and scratches.

[0003] Lead bronze is the most widely used among traditional copper-based sliding bearing alloys. However, due to the toxicity and pollution of lead, the use of lead-containing materials has been gradually restricted. Therefore, it is urgent to develop lead-free copper-based sliding bearing alloy powder. Graphite can replace lead as a lubricating phase to reduce friction. Currently, copper-based / graphite sliding bearing materials are mostly prepared by powder metallurgy, mechanical alloying and other methods, and are mostly integrally formed, which is not suitable for actual sliding bearing usage scenarios.

[0004] The use of laser cladding to prepare copper-based / graphite self-lubricating coatings is more flexible and more applicable, and the prepared coatings have a high bonding strength with the substrate. At the same time, there are also some technical difficulties in laser cladding of copper alloys. The reflectivity of copper alloys to lasers is very high, and the thermal conductivity and thermal expansion coefficient between copper and iron are quite different. During the laser cladding process, the heat of the cladding layer is easily dissipated, and it is difficult to form a good metallurgical bond. In addition, copper has low tension and high fluidity after melting, and strong hydrogen absorption at high temperatures, which makes the coatings formed by laser cladding prone to defects such as cracks and holes, which seriously affects the performance of the cladding layer. Therefore, the current research on the use of laser cladding to prepare copper-based / graphite self-lubricating coatings is not perfect. Summary of the invention

[0005] The purpose of the present invention is to provide a laser cladding copper-based self-lubricating coating applied to wind power sliding bearings and a preparation method thereof, so as to solve the above-mentioned problems.

[0006] In order to achieve the above object, the specific technical solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a laser cladding copper-based self-lubricating coating for wind power sliding bearings, wherein the coating comprises the following powder raw materials by mass percentage: 1-10% nickel-coated graphite and the remainder tin bronze.

[0008] Furthermore, the particle size of the tin bronze powder is 53-105 μm, and the particle size of the nickel-coated graphite powder is ≤75 μm.

[0009] Furthermore, the nickel-coated graphite powder consists of 60-95% nickel and 5-40% graphite in terms of mass percentage.

[0010] In the second aspect, the present invention provides a method for preparing the above-mentioned laser-clad copper-based self-lubricating coating applied to wind power sliding bearings. The method process is as follows: after weighing according to the ratio using a measuring balance, the tin bronze powder and the nickel-coated graphite powder are ball-milled and mixed using a planetary ball mill, the evenly mixed powder is dried and placed in a powder feeder, the surface of the substrate is treated and then laser-clad to obtain a copper-based self-lubricating coating.

[0011] Furthermore, the ball milling conditions are as follows: the ball milling beads are stainless steel balls, the ball-to-material mass ratio is 3:1, the ball mill speed is 150-300 r / min, and the ball milling time is 3-6 h.

[0012] Furthermore, the drying condition is drying in an oven at a temperature of 80 to 120° C. for 1.5 to 4 hours.

[0013] Furthermore, the substrate is made of 42CrMo steel and has a size of 150mm*120mm*10mm.

[0014] Furthermore, the substrate is processed by grinding the substrate surface with a grinding wheel to remove the oxide scale and make the substrate surface flat, and then cleaning with acetone to remove oil stains.

[0015] Furthermore, the parameters of the laser cladding are as follows: laser power of 800-2400W, scanning rate of 1.0-3.0m / min, powder feeding rate of 10-30g / min, overlap rate of 40-60%, shielding gas and powder feeding gas are both argon, and shielding gas flow rate is 15-25L / min.

[0016] The present invention has the following beneficial effects:

[0017] The present invention uses graphite as the lubricating phase to replace the lead element. Graphite has a close-packed hexagonal crystal structure, and the layers are connected by van der Waals force, and it is easy to slip when there is shear force. Therefore, during the friction and wear process, the graphite evenly distributed in the coating will be slowly squeezed to the surface of the material to form a lubricating film, thereby improving the friction reduction of the coating; and the graphite is coated with metal nickel to improve the interface bonding between the graphite and the copper matrix and reduce the ablation and oxidation of the graphite under the action of the high-energy laser beam.

[0018] On this basis, the present invention develops a friction-reducing copper alloy powder system for wind power sliding bearings by adding nickel-coated graphite to tin bronze, and uses a laser cladding method to prepare a copper-based / graphite self-lubricating coating with good forming, no cracks, low porosity and good bonding with the substrate, overcoming the technical difficulties of the current laser cladding process in the application of copper-based / graphite self-lubricating coatings. The hardness of the coating is improved compared with the pure tin bronze coating, and the friction reduction is significantly improved on the basis of ensuring wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 It is a cross-sectional view of the laser cladding copper-based coating prepared in Example 1 of the present invention and Comparative Example 1;

[0021] Figure 2 The Vickers hardness of the laser cladding copper-based coating prepared in Example 1 of the present invention and Comparative Example 1;

[0022] Figure 3 The friction coefficient and wear amount of the laser cladding copper-based coating prepared in Example 1 of the present invention and Comparative Example 1;

[0023] Figure 4 The friction coefficient and wear amount of the laser cladding copper-based coating prepared in Comparative Example 2 of the present invention;

[0024] Figure 5 This is a cross-sectional view of the laser cladding copper-based coating prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0025] The following is a detailed description of the powder material and preparation method of a laser-clad copper-based self-lubricating coating for wind power sliding bearings provided by the present invention.

[0026] The present invention provides a laser cladding copper-based self-lubricating coating for wind power sliding bearings, the coating comprising the following powder raw materials by mass percentage: 1-10% nickel-coated graphite, the balance is tin bronze. The nickel-coated graphite can be prepared by chemical nickel plating, or can be directly purchased. Tin bronze is a conventional known material and can be purchased.

[0027] For reference, the particle size of tin bronze powder is 53-105 μm, and the particle size of nickel-coated graphite powder is ≤75 μm.

[0028] For reference, nickel-coated graphite powder is composed of 60-95% nickel and 5-40% graphite by mass.

[0029] The present invention also provides a method for preparing the laser cladding copper-based self-lubricating coating applied to wind power sliding bearings, which specifically comprises the following steps:

[0030] (1) Preparation of mixed powder.

[0031] For example, a certain amount of tin bronze powder and nickel-coated graphite powder are weighed according to the mass fraction ratio, and the two powders are placed in a planetary ball mill, the ball milling beads are stainless steel balls, the ball-to-material mass ratio is 3:1, the ball mill speed is 150-300r / min, and the ball milling time is 3-6h. After the ball milling is completed, the mixed powder is placed in an oven at a temperature of 80-120°C and dried for 1.5-4h.

[0032] (2) Substrate pretreatment.

[0033] For reference, the substrate is made of 42CrMo steel with a size of 150mm*120mm*10mm. The substrate surface is polished with a grinding wheel to remove the oxide scale and make the substrate surface flat, and then cleaned with acetone to remove oil stains.

[0034] (3) Laser cladding.

[0035] As a reference, the substrate is fixed on the laser cladding workbench, and the evenly mixed and dried powder is placed in the powder feeder. The laser cladding process parameters are: laser power is 800-2400W, scanning rate is 1.0-3.0m / min, powder feeding rate is 10-30g / min, overlap rate is 40-60%, shielding gas and powder feeding gas are both argon, and shielding gas flow rate is 15-25L / min.

[0036] The preparation method of the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0037] Example 1

[0038] (1) Powder composition: The copper-based self-lubricating coating prepared in this embodiment is composed of 97% tin bronze and 3% nickel-coated graphite by mass percentage. The particle size of the tin bronze powder is 53-105 μm, and the particle size of the nickel-coated graphite powder is ≤75 μm. The nickel-coated graphite powder is composed of 70% nickel and 30% graphite by mass percentage.

[0039] (2) Preparation of mixed powder: Weigh tin bronze powder and nickel-coated graphite powder according to the mass fraction ratio, put the two powders into a planetary ball mill, the ball milling beads are stainless steel balls, the ball-to-powder mass ratio is 3:1, the ball mill speed is 190 r / min, and the ball milling time is 5 h.

[0040] (3) Powder drying treatment: Place the evenly mixed powder in an oven at 100°C and dry for 2 h.

[0041] (4) Substrate pretreatment: The substrate is made of 42CrMo steel with a size of 150 mm*120 mm*10 mm. The substrate surface is polished with a grinding wheel to remove the oxide scale and make the substrate surface flat, and then cleaned with acetone to remove oil stains.

[0042] (5) The substrate was fixed on the laser cladding workbench, and the evenly mixed and dried powder was placed in the powder feeder. The laser cladding process parameters were as follows: laser power of 1000 W, scanning rate of 2.0 m / min, powder feeding rate of 12 g / min, overlap rate of 50%, shielding gas and powder feeding gas were both argon, and the shielding gas flow rate was 25 L / min.

[0043] Comparative Example 1

[0044] (1) Powder composition: The coating prepared in Comparative Example 1 is a pure tin bronze coating without nickel-coated graphite, that is, the powder composition is 100% tin bronze powder with a particle size of 53 to 105 μm.

[0045] (2) Powder drying treatment: Place the tin bronze powder in an oven at 100°C and dry for 2 hours.

[0046] (3) Substrate pretreatment: The substrate is made of 42CrMo steel with a size of 150 mm*120 mm*10 mm. The substrate surface is polished with a grinding wheel to remove the oxide scale and make the substrate surface flat, and then cleaned with acetone to remove oil stains.

[0047] (4) Laser cladding: The substrate was fixed on the laser cladding workbench, and the evenly mixed and dried powder was placed in the powder feeder. The laser cladding process parameters were as follows: laser power of 1500 W, scanning rate of 2.0 m / min, powder feeding rate of 15 g / min, overlap rate of 50%, shielding gas and powder feeding gas were both argon, and the shielding gas flow rate was 25 L / min.

[0048] The cross-sectional view of the coating prepared in Example 1 is as follows Figure 1 (a) shows a cross-sectional view of the coating prepared in Comparative Example 1. Figure 1 As shown in (b); it can be seen that the coatings prepared in Example 1 and Comparative Example 1 are well formed, free of cracks, and have low porosity.

[0049] The hardness test was performed on Example 1 and Comparative Example 1. The Vickers hardness test was performed under the following conditions: the test force was 1.96 N and the loading time was 15 s. The results showed that the average microhardness of the copper-based / graphite self-lubricating coating prepared in Example 1 was 197.2 HV 0.2The average microhardness of the tin bronze self-lubricating coating prepared in Comparative Example 1 is 171.2 HV 0.2 ,like Figure 2 The copper-based / graphite self-lubricating coating prepared by the present invention has improved hardness compared with the pure tin bronze coating.

[0050] The friction and wear performance of Example 1 and Comparative Example 1 were tested. A vertical multifunctional friction and wear testing machine of model Rtec-Instruments MFT-5000 was used for the test. The test temperature was room temperature, the friction pair was a tungsten carbide ball with a diameter of 6 mm, the loading load was 25 N, the rotation radius was 6 mm, the speed was 100 r / min, and the test time was 120 min. After the test was completed, the mass difference before and after the wear of the sample was taken as the wear amount. The results showed that the friction coefficient of the copper-based / graphite self-lubricating coating prepared in Example 1 of the present invention was 0.32747, and the wear amount was 0.0011 g; the friction coefficient of the tin bronze self-lubricating coating prepared in Comparative Example 1 of the present invention was 0.37290, and the wear amount was 0.0011 g. Figure 3 Compared with the pure tin bronze coating, the copper-based / graphite self-lubricating coating prepared by the present invention has significantly improved friction reduction while ensuring wear resistance.

[0051] Comparative Example 2

[0052] The difference between this comparative example and Example 1 is that the nickel-coated graphite powder is composed of 100% graphite; the prepared coating is subjected to friction and wear tests, and the friction coefficient and wear amount are as follows: Figure 4 As shown. It can be seen that the friction coefficient of the coating is 0.39062, and the wear amount is 0.0036g. Compared with Example 1, the friction coefficient and wear amount of Comparative Example 1 are increased, and the friction and wear performance is reduced. Therefore, the friction and wear performance of the coating prepared by the cladding powder of this composition is not as good as the coating prepared by Example 1 of the present invention.

[0053] Comparative Example 3

[0054] The difference between this comparative example and Example 1 is that the copper-based self-lubricating coating is composed of 85% tin bronze and 15% nickel-coated graphite by mass percentage; a series of laser power ranges were tried, including laser power of 800W, 900W, 1000W, 1100W, etc., and the cross-sectional metallographic image of the obtained cladding layer is as follows Figure 5 As shown in the figure, it can be seen that no matter how large the energy input is, the dilution rate is large and the forming quality of the cladding layer is not ideal. Therefore, the forming property of the coating prepared by the cladding powder of this composition is very poor.

[0055] In summary, the copper-based self-lubricating composite coating prepared by the present invention has higher hardness than the pure tin bronze coating, and significantly improves the friction reduction property while ensuring the wear resistance.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A laser cladding copper-based self-lubricating coating applied to wind power sliding bearings, characterized in that: The coating comprises the following powder materials by mass percentage: 1-10% nickel-coated graphite and the remainder tin bronze.

2. The laser cladding copper-based self-lubricating coating for wind power sliding bearings according to claim 1 is characterized in that: The particle size of the tin bronze powder is 53-105 μm, and the particle size of the nickel-coated graphite powder is ≤75 μm.

3. The laser cladding copper-based self-lubricating coating for wind power sliding bearings according to claim 1 is characterized in that: The nickel-coated graphite powder consists of 60-95% nickel and 5-40% graphite in terms of mass percentage.

4. The method for preparing a laser cladding copper-based self-lubricating coating for wind power sliding bearings according to any one of claims 1 to 3, characterized in that: After weighing according to the ratio using a measuring balance, the tin bronze powder and the nickel-coated graphite powder are ball-milled and mixed using a planetary ball mill. The evenly mixed powder is dried and placed in a powder feeder. The surface of the substrate is treated and then laser cladding is performed to obtain a copper-based self-lubricating coating.

5. The method for preparing the laser cladding copper-based self-lubricating coating for wind power sliding bearings according to claim 4 is characterized in that: The ball milling conditions are as follows: the ball milling beads are stainless steel balls, the ball-to-material mass ratio is 3:1, the ball mill speed is 150-300 r / min, and the ball milling time is 3-6 h.

6. The method for preparing the laser cladding copper-based self-lubricating coating for wind power sliding bearings according to claim 4 is characterized in that: The drying condition is to dry in an oven at a temperature of 80 to 120° C. for 1.5 to 4 hours.

7. The method for preparing the laser cladding copper-based self-lubricating coating for wind power sliding bearings according to claim 4 is characterized in that: The substrate processing method comprises grinding the substrate surface with a grinding wheel to remove the oxide scale and make the substrate surface flat, and then cleaning with acetone to remove the oil stain.

8. The method for preparing the laser cladding copper-based self-lubricating coating for wind power sliding bearings according to claim 4 is characterized in that: The parameters of the laser cladding are as follows: laser power of 800-2400W, scanning rate of 1.0-3.0m / min, powder feeding rate of 10-30g / min, overlap rate of 40-60%, both shielding gas and powder feeding gas are argon, and shielding gas flow rate is 15-25L / min.

Citation Information

Patent Citations

  • Nickel-coated graphite self-lubricating composite material and application thereof

    CN103060614A

  • Laser cladding nickel-based cladding layer on surface of titanium alloy and preparation process thereof

    CN106756998A

  • High-performance copper-based solid self-lubricating composite material and preparation method thereof

    CN113718127A

  • Laser cladding copper-based self-lubricating material as well as preparation method and application thereof

    CN116162927A

  • Laser cladding material, material preparation method and laser cladding process method

    CN116618649A